Increased coronary sinus lactate concentration during pacing induced angina pectoris after clinical improvement by glyceryl trinitrate. Issue 5 (November 1983) - Bagger, J P; Nielsen, T T; Henningsen, P
Abstract : Ten patients with stable angina pectoris and obstructed coronary arteries (greater than 75% reduction in diameter) were studied before and during two periods of pacing, the second of which was preceded by sublingual administration of glyceryl trinitrate (mean dose 0.78 mg). Coronary sinus blood flow measurements and aortocoronary sinus blood sampling for metabolite determinations were carried out. Although the rate of pacing was increased by 10 beats/minute after glyceryl trinitrate administration, the onset of angina was delayed in eight patients during pacing. Drug administration decreased coronary sinus blood flow by 42% and myocardial oxygen uptake by 41% during pacing and induced a shift in mean lactate extraction towards a net release (from 3.1% to -12.6%). It increased the number of patients producing lactate from three to five. Glyceryl trinitrate administration decreased myocardial glucose uptake throughout the study, decreased lactate extraction during recovery, and increased the aortocoronary sinus citrate gradient at rest and during recovery, while the exchange of free fatty acids remained unchanged. A decrease in aortocoronary sinus lactate difference during pacing after glyceryl trinitrate administration correlated positively with the fall in coronary sinus blood flow. The metabolic data do not indicate an augmented myocardial lactate production after glyceryl trinitrate administration. A decrease in coronary sinus blood flow seems, therefore, to be of primary importance in explaining the elevated coronary sinus lactate concentration. Our finding that coronary sinus lactate concentration increased during pacing after glyceryl trinitrate administration despite clinical improvement questions the validity of its use as a quantitative index of ischaemia.